High School Students’ Interests, Difficulties, and Conceptual Understanding of Cell Concepts - Luthfyanti, Juanita; Lutfi, Anas; Sari, Indah Juwita; Aberilla, Odessa (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2024)
The purpose of this study was to determine the learning interests, difficulties, and conceptual understanding of high school students on cell concepts. The study was conducted at one of the state high schools in Serang. The study cohort comprised 71 students enrolled in class XI, specializing in Mathematics and Natural Sciences, and a teacher in Biology.  The data collection methodology employed in this research involved conducting structured interviews with the biology educator and survey questionnaires among students. The stages in carrying out data analysis are data reduction, data display, and the iterative process of drawing conclusions and verification. The results of this research showed the importance of students' conceptual understanding of cell concepts, as evidenced in the data analysis of students who have a low level of conceptual understanding. The low understanding of the concept is caused by several factors, including cell concepts being too complex and abstract, dominant learning not being interactive, cell concepts being conceptual, and difficulty understanding foreign languages or Latin. Based on the results of interviews with biology teachers, several obstacles result in students' low conceptual understanding of cell concepts, including students being less interested in seeking additional explanations regarding cell concepts, students having low memory ability in studying the lesson concepts that has been presented by the teacher, and still a lack of availability of teaching aids in schools for cell concepts.